Amyand’s Hernia: A Rare Case Report - Fadli Robby Amsriza; Rizka Fakhriani (Berkala Kedokteran, 2021)
Abstract: Amyand’s hernia is described in the inguinal hernia sac as being the presence of an appendix vermiformis. It is a rare condition the incidence is about 1 per cent of all inguinal hernias. It is often diagnosed incidentally during inguinal hernia surgery. The main treatment method of Amyand’s hernia is surgery. We report a case of 63 years old man who presented with right inguinal groin bulge for 1 month with the previous repaired right inguinal hernia 5 years ago. On clinical examination revealed a 6 cmx8 cm firm, nontender, irreponible mass in the right inguinal region. He was diagnosed as right sided irreponible inguinal hernia. He was undergoing the elective surgery. Intra-operative, the hernia sac was laterally found in the inferior epigastric vessels and separated from sperm cord to deep inguinal ring. The hernia sac was opened. A non-inflamed appendix was seen. Appendectomy was performed, and the hernia was repaired by Halsted’s repair. Amyand’s hernia is a rare condition. The correct diagnosis is usually made intraoperative.   Keywords: Amyand’s hernia, appendectomy, hernia repair, inguinal hernia.